Youth risk-taking behavior in Brazil: drug use and teenage pregnancies - Ana Rute Cardoso; Dorte Verner (Institute for the Study of Labor (IZA), 2007)
Using an extensive survey addressing risk factors faced by the population in the shantytowns of Fortaleza, Brazil, the aim of this paper is to study interactions among different types of risk-taking behavior by youth, namely drug use and teenage pregnancy. We check the impact of factors such as exposure to mass media, the existence of support networks, self-esteem, or the occurrence of violence at home and in the neighborhood, on the probability of risk-taking behavior. A bivariate probit model is estimated. Findings indicate that reliance on support networks and exposure to mass media are associated with a lower probability of either type of risk behavior. Living in a violent home increased drug consumption. Race does not have a significant impact on either type of behavior.
Keywords: 360; Drug use; teenage pregnancy; sexual behavior; reproductive health; teenage behavior; Jugendliche; Risikopräferenz; Drogenkonsum; Schwangerschaft; Sozialpsychologie; Brasilien